Role of nano and micron-sized inclusions on the oxygen controlled preform optimized infiltration growth processed YBCO superconductors. (February 2017) - Pavan Kumar Naik, S.; Bai, V. Seshu
Abstract: In the present work, with the aim of improving the local flux pinning at the unit cell level in the YBa2 Cu3 O7-δ (YBCO) bulk superconductors, 20 wt% of nanoscale Sm2 O3 and micron sized (Nd, Sm, Gd)2 BaCuO5 secondary phase particles were added to YBCO and processed in oxygen controlled preform optimized infiltration growth process. Nano Dispersive Sol Casting method is employed to homogeneously distribute the nano Sm2 O3 particles of 30–50 nm without any agglomeration in the precursor powder. Microstructural investigations on doped samples show the chemical fluctuations as annuli cores in the 211 phase particles. The introduction of mixed rare earth elements at Y-site resulted in compositional fluctuations in the superconducting matrix. The associated lattice mismatch defects have provided flux pinning up to large magnetic fields. Magnetic field dependence of current density (Jc (H)) at different temperatures revealed that the dominant pinning mechanism is caused by spatial variations of critical temperatures, due to the spatial fluctuations in the matrix composition. As the number of rare earth elements increased in the YBCO, the peak field position in the scaling of the normalized pinning force density (Fp /Fp max ) significantly gets shifted towards the higher fields. The curves of Jc (H) and Fp /Fp max at different temperatures clearly indicate the LRE substitution for LRE' or Ba-sites for δTc pinning. Highlights: Effect of the addition of nano Sm2O3 and micron sized (Nd, Sm, Gd)2BaCuO5 inclusions on YBCO is studied. All the samples are synthesized in oxygen controlled preform optimized infiltration growth process. Microstructural features of the doped samples show the compositional segregations in the precipitates. The Jc(0) of (Y, Nd, Sm, Gd)BCO is 21500 A/cm2 at 77 K and remained better than 300 A/cm2 even at 9 T field.